Putrescine Depletion in Leishmania donovani Parasites Causes Immediate Proliferation Arrest Followed by an Apoptosis-like Cell Death - Julia Johnston; Jonathan Taylor; Surbhi Nahata; Angelica Gatica-Gomez; Yvette L. Anderson; Sophia Kiger; Thong Pham; Kayhan Karimi; Jasmin-Faith Lacar; Nicola S. Carter; Sigrid C. Roberts (Pathogens)
The polyamine pathway in Leishmania parasites has emerged as a promising target for therapeutic intervention, yet the functions of polyamines in parasites remain largely unexplored. Ornithine decarboxylase (ODC) and spermidine synthase (SPDSYN) catalyze the sequential conversion of ornithine to putrescine and spermidine. We previously found that Leishmania donovani Δodc and Δspdsyn mutants exhibit markedly reduced growth in vitro and diminished infectivity in mice, with the effect being most pronounced in putrescine-depleted Δodc mutants. Here, we report that, in polyamine-free media, ∆odc mutants arrested proliferation and replication, while ∆spdsyn mutants showed a slow growth and replication phenotype. Starved ∆odc parasites also exhibited a marked reduction in metabolism, which was not observed in the starved ∆spdsyn cells. In contrast, both mutants displayed mitochondrial membrane hyperpolarization. Hallmarks of apoptosis, specifically DNA fragmentation and membrane modifications, were observed in Δodc mutants incubated in polyamine-free media. These results show that putrescine depletion had an immediate detrimental effect on cell growth, replication, and mitochondrial metabolism and caused an apoptosis-like death phenotype. Our findings establish ODC as the most promising therapeutic target within the polyamine biosynthetic pathway for treating leishmaniasis.